2021
DOI: 10.1371/journal.pone.0252874
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of disease in cynomolgus monkeys exposed to Ebola virus Kikwit strain demonstrates the reliability of this non-human primate model for Ebola virus disease

Abstract: Filoviruses (Family Filoviridae genera Ebolavirus and Marburgvirus) are negative-stranded RNA viruses that cause severe health effects in humans and non-human primates, including death. Except in outbreak settings, vaccines and other medical countermeasures against Ebola virus (EBOV) will require testing under the FDA Animal Rule. Multiple vaccine candidates have been evaluated using cynomolgus monkeys (CM) exposed to EBOV Kikwit strain. To the best of our knowledge, however, animal model development data supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…The replication-competent rVSV∆G-MARV-GP vaccine has been shown to be safe and highly efficacious in earlier preclinical studies [ 27 , 33 , 37 , 38 , 39 , 40 , 41 , 46 , 55 ], and we have developed a new recombinant virus and pre-MVS under conditions that will support production of vaccine material for use in human trials. Using this new rVSV∆G-MARV-GP, we have replicated the previous results showing that a single-dose of around 2 × 10 7 PFUs is 100% efficacious and have extended the earlier data by showing that potent protection is achieved using much lower doses in cynomolgus macaques, a well-characterized filovirus disease model [ 42 , 43 , 62 , 63 ]. We found that a single dose of as little as 200 PFUs of rVSV∆G-MARV-GP (Musoke) prevented development of clinical signs of MARV disease ( Figure 3 A) following challenge with the more virulent Angola MARV variant [ 44 ].…”
Section: Discussionsupporting
confidence: 77%
“…The replication-competent rVSV∆G-MARV-GP vaccine has been shown to be safe and highly efficacious in earlier preclinical studies [ 27 , 33 , 37 , 38 , 39 , 40 , 41 , 46 , 55 ], and we have developed a new recombinant virus and pre-MVS under conditions that will support production of vaccine material for use in human trials. Using this new rVSV∆G-MARV-GP, we have replicated the previous results showing that a single-dose of around 2 × 10 7 PFUs is 100% efficacious and have extended the earlier data by showing that potent protection is achieved using much lower doses in cynomolgus macaques, a well-characterized filovirus disease model [ 42 , 43 , 62 , 63 ]. We found that a single dose of as little as 200 PFUs of rVSV∆G-MARV-GP (Musoke) prevented development of clinical signs of MARV disease ( Figure 3 A) following challenge with the more virulent Angola MARV variant [ 44 ].…”
Section: Discussionsupporting
confidence: 77%
“…Our primary goal in this study was to determine if an analogous model using MARV as the challenge agent was similarly adaptable for evaluation of countermeasures. Analogous to the observation in cynomolgus macaques infected with either Ebola or Sudan filoviruses [ 20 , 22 , 23 ], a short refractory period with few signs of disease was followed by increasing clinical scores starting at Day 5 post challenge for some animals and increasing rapidly for all infected animals on subsequent days. The median time to death was 7.3 days post-challenge.…”
Section: Discussionsupporting
confidence: 52%
“…Mauritian cynomolgus macaques have more rapid disease progression after Ebola virus infection compared with cynomolgus macaques of Cambodian origin. 43 This is believed to be mediated by differences in immune cell populations and microbiota, 43 45 with a likely contribution of their divergent genetics, which may include divergence in FcR sequence and functionality. 46 48 However, the reduced efficacy observed in this study does replicate observations in humans of reduced vaccine efficacy at later time points and presents a unique opportunity to investigate antibody-mediated correlates of protection after rVSVΔG-ZEBOV-GP vaccination.…”
Section: Discussionmentioning
confidence: 99%